1999
DOI: 10.1152/ajpheart.1999.276.1.h224
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 72-kDa heat shock protein does not produce second window of ischemic preconditioning in rat heart

Abstract: Ischemic preconditioning (PC) induces delayed phase of protection, known as the second window of protection (SWOP). We investigated this phenomenon in rat and correlated it with the expression of 72-kDa heat shock protein (HSP 72). Rats were preconditioned with 1, 2, and 3 cycles of 5-min left anterior descending artery occlusions, each separated by a 10-min reperfusion (PC × 1, PC × 2 and PC × 3, respectively). Another group of rats was preconditioned with heat shock (HS) by raising temperature to 42°C for 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…Moreover, two previous studies suggest that expression of inducible HSP70 following IP does not provide protection against ischemia, as assessed by a reduction in infarct size. Using a rat model of myocardial I/R, Qian et al (32) reported that IP, despite enhancing expression of myocardial HSP72, did not provide late protection against infarction following regional ischemia. Also, Tanaka et al (39) observed that IP failed to reduce infarction after prolonged ischemia in rabbits despite increased expression of HSP72-73 induced by IP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two previous studies suggest that expression of inducible HSP70 following IP does not provide protection against ischemia, as assessed by a reduction in infarct size. Using a rat model of myocardial I/R, Qian et al (32) reported that IP, despite enhancing expression of myocardial HSP72, did not provide late protection against infarction following regional ischemia. Also, Tanaka et al (39) observed that IP failed to reduce infarction after prolonged ischemia in rabbits despite increased expression of HSP72-73 induced by IP.…”
Section: Discussionmentioning
confidence: 99%
“…There is now compelling genetic and biochemical evidence that these proteins belong to a family of ATP-dependent "unfoldases" implicated in protein assembly/dissociation of multimeric complexes, translocation, and import/export processes across membranes. 3 It is well established that preconditioning with brief episodes of ischemia, 4 -6 as well as other forms of stress, such as heat shock, [5][6][7][8] result in increased production of HSP 70 in the heart. The amount of HSP 70 synthesis correlates with the extent of myocardial protection after ischemia/reperfusion injury.…”
mentioning
confidence: 99%
“…Qian et al (23) have shown that in rats ischemic preconditioning does not induce delayed cardioprotection, even though levels of HSP70 are comparable with those observed after whole body hyperthermia. In addition, Taylor et al (31) show that exercise alone without HSP induction confers protection.…”
Section: Discussionmentioning
confidence: 88%